The national performance review in perspective - Pfiffner, James P. (1997)
The National Performance Review was one of the most ambitious, far-reaching and thoroughly prepared management reform efforts of the twentieth century. This article examines some of the main themes and principles of the NPR. It begins with the Clinton administration's marketing of the effort and goes on to analyze the arguments of its major scholarly critics. It then presents the more practical public management critiques of the NPR implementation. The article concludes with a comparison of the most important contributions and drawbacks of the total effort and delineates the public management dilemmas that the NPR presents to federal managers. - Reproduced
Keywords: Administrative reform - United States; Public administration - United States; Administrative reform